Organosilicon material containing Si-H substituent and ethyl substituent, preparation method and application

Through the equilibrium polymerization process of acidic chlorinated phosphazene acid catalyst, silicone materials with Si-H and ethyl substituents were successfully prepared, which solved the problems of insufficient material performance and safety hazards in the prior art, and achieved structural uniformity and stability, expanding the application field.

CN119192580APending Publication Date: 2024-12-27HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271257.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

It is difficult to prepare silicone materials with Si-H and ethyl substituents in the prior art, resulting in insufficient performance in low-temperature environments, and safety hazards and dimensional shrinkage problems in the preparation process.

Method used

The Si-H and ethyl substituents are prepared by an equilibrium polymerization process using an acidic chlorinated phosphazene acid catalyst to ensure the structural uniformity and narrow molecular weight distribution of the material and avoid dehydrogenation coupling reactions.

Benefits of technology

Overcoming the problem of Si-H incompatibility with alkaline catalysts, the preparation of silicone materials containing both Si-H and ethyl substituents in the molecule is realized, with good fluidity and stability, suitable for addition silicon Rubber crosslinking agents have expanded the application field of ethyl silicone materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192580A_ABST
    Figure CN119192580A_ABST
Patent Text Reader

Abstract

The invention discloses an organosilicon material containing Si-H substituent and ethyl substituent and a preparation method and application thereof, the structure of the organosilicon material is as shown in formula (A), in the formula (A), R1 is methyl, ethyl, phenyl, trifluoropropyl or H; r2 is methyl, ethyl, phenyl or trifluoropropyl; r3 is an ethyl group; r4 is methyl, phenyl or trifluoropropyl; r5 is methyl, phenyl, trifluoropropyl or H; m is the polymerization degree of the R2R3SiO chain link, and the value of m is 3-100; n is the polymerization degree of the R4R5SiO chain link, and the value is 0-50; at least one of R1 and R5 is H. The organosilicon material is prepared by taking the chlorinated phosphazene acid as the catalyst, taking the disiloxane containing the Si-H substituent group and / or the methyl hydrogen cyclosiloxane polymeric monomer as a Si-H group source and taking the cyclosiloxane containing the ethyl substituent group as an ethyl group source, the process is simple, the dosage of the catalyst is small, the molecular weight distribution of the prepared organosilicon material is narrow, and the preparation process is simple. The chain segment is uniform in structure and can be used as a cross-linking agent for hydrosilylation reaction. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to an organic silicon material containing a Si-H substituent and an ethyl substituent, a preparation method and an application thereof. Background Art

[0002] Silicone polymer materials have excellent properties such as high and low temperature resistance, weather resistance, UV resistance, hydrophobicity, and hydrophobic migration, and are widely used in various sectors and fields of the national economy. Depending on the active functional groups in the molecules, application scenarios, and processing capabilities, silicone polymer materials can be cured by room temperature condensation vulcanization, free radical addition vulcanization initiated by peroxide compounds at high temperatures, and hydrosilylation vulcanization catalyzed by platinum coordination complexes under mild conditions. Among them, platinum-catalyzed hydrosilylation vulcanization has the characteristics of mild reaction conditions, small product size shrinkage before and after reaction vulcanization, and no odor in the product. It is especially suitable for in-situ molding processes and is a new product that has been focused on in the field of silicone products in recent years.

[0003] The platinum-catalyzed hydrosilylation reaction requires an organosilicon polymer material containing silyl vinyl (Si-CH=CH2) and silyl hydride (Si-H) functional groups as a reaction substrate. Usually, the organosilicon polymer material containing silyl hydride functional groups is also called a crosslinker for the hydrosilylation reaction, and the component containing silyl vinyl functional groups is called a polymer matrix material.

[0004] Silicone polymers whose polymer backbones are all composed of dimethylsiloxy chain segments (Me2SiO) are the most common silicone materials, accounting for 95% or more of all silicone materials on the market. Although silicone polymer materials composed of dimethylsiloxy chain segments have the aforementioned excellent physical and chemical properties, the glass transition temperature of such polymer materials is around -122°C, making them difficult to be used in aerospace, pharmaceutical and other application fields that have higher requirements for low-temperature performance of materials.

[0005] The polydiethylsiloxane polymer obtained by replacing all the methyl functional groups in the silicone polymer material with ethyl groups has a glass transition temperature as low as -143°C, which is the material with the lowest glass transition temperature among the synthetic polymer materials known today. Therefore, the ethyl silicone polymer material prepared by the hydrosilylation reaction has a lower service temperature environment in the field of low-temperature materials than the silicone material composed of pure methyl.

[0006] Like methyl silicone polymer materials, silicone polymer materials containing ethyl groups or composed entirely of ethyl groups can also be vulcanized and formed by hydrosilylation reaction to form a three-dimensional spatial network structure. However, due to the large difference in the chemical properties of ethyl groups and methyl groups, especially the more significant electron-donating ability of ethyl groups, polymer monomers containing ethyl functional groups, such as hexaethylcyclotrisiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane, have low reactivity. KOH (Polymer, 35, (1994), 5118-5123.), linear or cyclic phosphazene superbase (Macromolecules, 2022, 55 (7): 2844-2853) must be used as catalysts and reacted under certain temperature conditions to obtain silicone polymer materials containing ethyl substituents. Since the silyl vinyl functional group (Si-CH=CH2) can exist stably under alkaline conditions, when the above catalyst is used, silicone polymer materials containing silyl vinyl functional groups and ethyl substituents can be successfully prepared.

[0007] However, since Si-H bonds can easily induce dehydrogenation coupling reactions under alkaline conditions, compounds or polymers containing Si-H bonds will produce a large amount of hydrogen or even explode when encountering strong alkali, posing serious safety hazards. As a result, silicone polymer materials containing Si-H bonds can only be prepared under acidic conditions. For example, methyl hydrogen-containing silicone oil, phenyl hydrogen-containing silicone oil, benzyl hydrogen-containing silicone oil, etc. containing Si-H functional groups and methyl or phenyl functional groups are all prepared using acidic catalysts such as acidic ion exchange resins, solid superacids, sulfuric acid, and trifluoromethanesulfonic acid.

[0008] Since the ethyl group has an electron donating effect different from that of the methyl and phenyl groups, it is difficult to cause the polymer monomers containing diethyl siloxane chains or methylethyl siloxane chains to undergo ring-opening polymerization when the above-mentioned acidic catalyst is used. Therefore, there are few reports in the literature on organosilicon materials containing Si-H and ethyl substituents. As a result, to date, organosilicon polymer materials containing ethyl substituents cannot be cured by hydrosilylation, and can only be formed by room temperature condensation vulcanization or high temperature vulcanization to form a cross-linked cured network.

[0009] Although room temperature condensation-vulcanized ethyl silicone materials can be formed in situ, the condensation reaction releases small molecules such as alcohol, ketone, ketoxime, acetic acid, etc., which will cause the cured material to shrink in size or have pores, seriously affecting the performance of the device; ethyl-containing silicone polymer materials prepared by high-temperature vulcanization can only be prepared by pre-vulcanization molding to obtain parts of a certain shape, which cannot meet the working conditions required for in situ molding.

[0010] In summary, the research and development of silicone polymer materials containing Si-H and ethyl substituents is the key to the development of addition-type ethyl silicone materials. Summary of the invention

[0011] In order to overcome the current inability to prepare a uniformly structured organosilicon material containing both Si-H and ethyl substituents in the molecule, and to provide a crosslinking agent with the ethyl content required for the hydrosilylation reaction for the addition-type ethyl organosilicon material, the present invention provides an organosilicon material containing Si-H and ethyl substituents, a preparation method and application. The organosilicon material of the present invention has a uniform segment structure, a narrow molecular weight distribution, and contains both Si-H and ethyl substituents. It has a simple preparation process, a small amount of catalyst, low cost, mild reaction and post-treatment conditions, and is easy to scale up industrially.

[0012] The first aspect of the present invention provides an organic silicon material containing a Si-H substituent and an ethyl substituent, having a structure shown in the following formula:

[0013]

[0014] Among them, R1 is methyl, ethyl, phenyl, trifluoropropyl or H; R2 is methyl, ethyl, phenyl or trifluoropropyl; R3 is ethyl; R4 is methyl, phenyl, trifluoropropyl; R5 is methyl, phenyl, trifluoropropyl or H; m is the degree of polymerization of the R2R3SiO chain segment, which is 3 to 100; n is the degree of polymerization of the R4R5SiO chain segment, which is 0 to 50; at least one of R1 and R5 is H.

[0015] The second aspect of the present invention provides a method for preparing the organic silicon material containing Si-H substituents and ethyl substituents, comprising the following steps:

[0016] Under the protection of inert gas, a capping agent, a polymerizable monomer and a chlorophosphonitrile acid catalyst are added to a reactor, stirred, and a balanced polymerization reaction is carried out to obtain the organic silicon material containing Si-H substituents and ethyl substituents, wherein the capping agent is a disiloxane containing Si-H substituents or a disiloxane without Si-H substituents; the polymerizable monomer is at least one of a cyclosiloxane containing an ethyl substituent, a polymerizable monomer containing a dimethylsiloxy chain segment (Me2SiO), a polymerizable monomer containing a methylphenylsiloxy chain segment (MePhSiO), a polymerizable monomer containing a methyltrifluoropropylsiloxy chain segment (Me(CF3CH2CH2)SiO), a diphenylsiloxy chain segment (Ph2SiO) or a methylhydrogencyclosiloxane polymerizable monomer, and in the combination of the capping agent and the polymerizable monomer, at least one compound contains a Si-H group and at least one compound contains an ethyl substituent.

[0017] The invention uses linear chlorophosphonitrile acid as a catalyst, disiloxane containing Si-H substituents and / or methylhydrogen cyclosiloxane polymerization monomers as Si-H group sources, cyclosiloxane containing ethyl substituents as ethyl group sources, monomers containing dimethylsiloxane chain segments (Me2SiO), and / or monomers containing methylphenylsiloxane (MePhSiO) chain segments, and / or monomers containing diphenylsiloxane (Ph2SiO) chain segments, and / or monomers containing methyltrifluoropropylsiloxane chain segments (Me(CF3CH2CH2)SiO) as polymerization monomers of the main chain of the organosilicon material, and prepares a linear organosilicon polymer containing both Si-H and Si-CH2CH3 (silicon ethyl) in the molecule through an acid-catalyzed equilibrium polymerization process.

[0018] Specifically, when the end-capping agent is a disiloxane containing a Si-H substituent, the polymer monomer is a cyclosiloxane containing an ethyl substituent; or a mixture of a cyclosiloxane containing an ethyl substituent and other polymer monomers, wherein the other polymer monomers are at least one of a polymer monomer containing a dimethylsiloxy chain segment, a polymer monomer containing a methylphenylsiloxy chain segment (MePhSiO), a polymer monomer containing a methyltrifluoropropylsiloxy chain segment (Me(CF3CH2CH2)SiO), a polymer monomer containing a diphenylsiloxy chain segment (Ph2SiO) or a methylhydrogencyclosiloxane polymer monomer;

[0019] When the end-capping agent is a disiloxane without Si-H substituent, the polymerized monomer is a mixture of a cyclosiloxane containing an ethyl substituent and a methyl hydrogen cyclosiloxane polymerized monomer; or a mixture of a cyclosiloxane containing an ethyl substituent and a methyl hydrogen cyclosiloxane polymerized monomer and other polymerized monomers, wherein the other polymerized monomer is at least one of a polymerized monomer containing a dimethyl siloxane chain segment, a polymerized monomer containing a methyl phenyl siloxane chain segment (MePhSiO), a polymerized monomer containing a methyl trifluoropropyl siloxane chain segment (Me(CF3CH2CH2)SiO) or a polymerized monomer containing a diphenyl siloxane chain segment (Ph2SiO). Under the above conditions, the obtained polymer structure contains both Si-H and ethyl substituents.

[0020] Preferably, the inert gas is selected from at least one of nitrogen, argon or helium.

[0021] Preferably, the Si-H substituted disiloxane is selected from at least one of 1,1,3,3-tetramethyldisiloxane and 1,1,1,3,3-pentamethyldisiloxane.

[0022] Preferably, the disiloxane containing no Si-H substituent is selected from at least one of hexamethyldisiloxane, octamethyltrisiloxane, decamethyltetrasiloxane, 1,1,3,3-tetramethyl-1,3-diphenyldisiloxane, or 1,1-dimethyl-1,1,3,3-tetraphenyldisiloxane.

[0023] Preferably, the cyclosiloxane containing an ethyl substituent includes at least one of hexaethylcyclotrisiloxane, octaethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-triethylcyclotrisiloxane or 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane.

[0024] Preferably, the polymerized monomer containing dimethylsiloxy chain segments includes at least one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, tetradecamethylcycloheptasiloxane, hexadecamethylcyclooctasiloxane, octamethylcyclononasiloxane, eicosylcyclodecasiloxane or a mixed cyclosiloxane (DMC) composed of dimethylsiloxy chain segments.

[0025] Preferably, the polymerized monomer containing methylphenylsiloxy chain segments (MePhSiO) comprises at least one of cis- and trans-1,3,5-trimethyl-1,3,5-triphenylcyclotrisiloxane and mixtures thereof, four isomers of 1,3,5,7-tetramethyl-1,3,5,7-tetraphenylcyclotetrasiloxane and mixtures thereof, and four isomers of 1,3,5,7,9-pentamethyl-1,3,5,7,9-pentaphenylcyclopentasiloxane and mixtures thereof.

[0026] Preferably, the polymerized monomer containing methyltrifluoropropylsiloxy chain segments (Me(CF3CH2CH2)SiO) includes at least one of cis- and trans-1,3,5-trimethyl-1,3,5-tri(trifluoropropyl)cyclotrisiloxane and mixtures thereof, four isomers of 1,3,5,7-tetramethyl-1,3,5,7-tetra(trifluoropropyl)cyclotetrasiloxane and mixtures thereof, and four isomers of 1,3,5,7,9-pentamethyl-1,3,5,7,9-penta(trifluoropropyl)cyclopentasiloxane and mixtures thereof.

[0027] Preferably, the polymerizable monomer containing diphenylsiloxy chain segments (Ph2SiO) includes at least one of hexaphenylcyclotrisiloxane, octaphenylcyclotetrasiloxane and decaphenylcyclopentasiloxane.

[0028] Preferably, the methylhydrogencyclosiloxane includes at least one of 1,3,5-trimethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5-trimethylcyclotetrasiloxane, 1,3-dimethylcyclotetrasiloxane, 1,5-dimethylcyclotetrasiloxane, 1,3,5,7,9-pentamethylcyclopentasiloxane or 1,3,5,7,9,11-hexamethylcyclohexasiloxane.

[0029] In the preparation process of the organic silicon material containing Si-H substituents and ethyl substituents of the present invention, at least one Si-H substituent comes from a capping agent or a methylhydrogen cyclosiloxane polymerization monomer.

[0030] Preferably, the molar ratio of the end-capping agent to the polymerized monomer is 0.05 to 1:1. More preferably, the molar ratio of the end-capping agent to the polymerized monomer is 0.15 to 1:1. Within this feeding range, the viscosity of the prepared organic silicon material containing Si-H substituents and ethyl substituents is less than 4000 mPa.s, has good fluidity, and can meet the technical requirements of addition-type silicone rubber crosslinking agents.

[0031] Preferably, the ratio of the effective mass of the chlorophosphonitrile acid catalyst to the sum of the mass of the end-capping agent and the polymerized monomer is (10-2000)×10 -6 More preferably, the ratio of the chlorophosphazene acid catalyst to the sum of the mass of the end-capping agent and the polymerizable monomer is (200-1000)×10 -6 :1.

[0032] The present invention uses acidic phosphonitrile chloride as a catalyst for the ring-opening polymerization of cyclosiloxane containing ethyl substituents to prepare an organosilicon material containing Si-H substituents and ethyl substituents, thereby overcoming the problem that the organosilicon material containing Si-H substituents and ethyl substituents cannot be prepared due to the incompatibility of Si-H with alkaline catalysts, and has high catalytic ring-opening efficiency, simple and controllable reaction process, narrow molecular weight distribution of the prepared polymer, and good stability. In addition, the catalyst phosphonitrile chloride used in the present invention has a small amount of acid, a simple catalyst preparation method, and low cost.

[0033] Preferably, the equilibrium polymerization reaction temperature is 40-120°C, and the reaction time is 4-12 hours. More preferably, the equilibrium polymerization reaction temperature is 50-100°C, and the reaction time is 5-11 hours.

[0034] Preferably, the preparation method further comprises, after the equilibrium polymerization reaction is completed, adding a passivating agent to the reaction system to neutralize the chlorophosphazene acid to obtain a crude reaction product; then removing the reactants and oligomers that have not been completely reacted in the crude reaction product, and then filtering under reduced pressure to remove the solid residue in the product to obtain the organosilicon material containing Si-H substituents and ethyl substituents.

[0035] Preferably, the passivating agent is at least one of hexamethyldisilazane, magnesium oxide, aluminum oxide, zinc oxide or ferric oxide, and the ratio of the mass of the passivating agent to the effective mass of the chlorophosphazenic acid catalyst is 3 to 10: 1. More preferably, the ratio of the mass of the passivating agent to the effective mass of the chlorophosphazenic acid catalyst is 5 to 10: 1.

[0036] Preferably, the stirring time after adding the passivating agent is 3 to 24 hours, so that the chlorophosphazene acid catalyst is fully neutralized.

[0037] More preferably, the passivating agent is hexamethyldisilazane, and the stirring time after adding the passivating agent is 5 to 12 hours.

[0038] Preferably, the conditions for removing the unreacted reactants and oligomers in the crude reaction product are: removal temperature 150 to 250° C., system vacuum degree -101.3 to -90 kPa, and removal time 4 to 12 h.

[0039] The third aspect of the present invention provides the use of the organosilicon material containing Si-H substituents and ethyl substituents as a crosslinking agent in the preparation of organosilicon polymer materials or composite materials. The organosilicon material containing Si-H substituents and ethyl substituents of the present invention has a uniform structure and good stability, and can be used as a crosslinking agent for addition-type ethyl organosilicon materials by using a hydrosilylation method to prepare an organosilicon polymer material or composite material that does not shrink after crosslinking and curing, has a low glass transition temperature, and can be formed in situ.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The present invention uses linear chlorophosphonitrile acid as a catalyst, disiloxane or methylhydrogen cyclosiloxane polymerization monomers containing Si-H substituents as Si-H group sources, cyclosiloxane containing ethyl substituents as ethyl group sources, and monomers containing dimethylsiloxy chain segments (Me2SiO), methylphenylsiloxy chain segments (MePhSiO), methyltrifluoropropylsiloxy chain segments (Me(CF3CH2CH2)SiO) or diphenylsiloxy chain segments (Ph2SiO) as polymerization monomers of the main chain of the organosilicon material, and prepares a linear organosilicon polymer containing both Si-H and Si-CH2CH3 in the molecule through an acid-catalyzed equilibrium polymerization process, thereby overcoming the shortcomings of the prior art that the organosilicon ring containing ethyl has poor reactivity, Si-H will dehydrogenate and couple with alkaline substances, and a polymer containing Si-H cannot be obtained;

[0042] (2) The catalyst used in the present invention is a small amount of chlorophosphazene acid, the catalyst preparation method is simple, and the cost is low;

[0043] (3) The reaction and post-treatment conditions of the present invention are mild, the process is simple, and it is easy to realize industrialization;

[0044] (4) The organosilicon polymer material containing Si-H and ethyl substituents prepared by the present invention has a uniform structure, good stability, a single polymer structure, and a narrow molecular weight distribution. It can be used as a crosslinking agent for addition-type ethyl organosilicon materials, thereby expanding the application field of ethyl organosilicon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 For the product prepared in Example 2 1 H NMR spectrum.

[0046] Figure 2 For the product prepared in Example 2 13 C NMR spectrum.

[0047] Figure 3 For the product prepared in Example 2 29 Si NMR spectrum.

[0048] Figure 4 This is the GPC curve of the product prepared in Example 2.

[0049] Figure 5 For the product prepared in Example 3 1 H NMR spectrum.

[0050] Figure 6 For the product prepared in Example 3 13 C NMR spectrum.

[0051] Figure 7 For the product prepared in Example 3 29 Si NMR spectrum.

[0052] Figure 8 For the product prepared in Example 4 1 H NMR spectrum.

[0053] Fig. 9 For the product prepared in Example 4 13 C NMR spectrum.

[0054] Fig.10 For the product prepared in Example 4 29 Si NMR spectrum.

[0055] Fig.11 For the product prepared in Example 5 1 H NMR spectrum.

[0056] Fig.12 For the product prepared in Example 5 13C NMR spectrum.

[0057] Fig.13 For the product prepared in Example 5 29 Si NMR spectrum.

[0058] Fig.14 For the product prepared in Example 6 1 H NMR spectrum.

[0059] Fig.15 This is the GPC curve of the product prepared in Example 6.

[0060] Fig.16 For the product prepared in Comparative Example 1 1 H NMR spectrum.

[0061] Fig.17 For the product prepared in Comparative Example 1 13 C NMR spectrum.

[0062] Fig.18 For the product prepared in Comparative Example 1 29 Si NMR spectrum.

[0063] Fig.19 This is the GPC curve of the product prepared in Comparative Example 1.

[0064] Fig. 20 For the product prepared in Comparative Example 2 1 H NMR spectrum.

[0065] Fig.21 For the preparation of the product in Comparative Example 2 13 C NMR spectrum.

[0066] Fig. 22 For the preparation of the product in Comparative Example 2 29 Si NMR spectrum.

[0067] Fig.23 This is the GPC curve of the product prepared in Comparative Example 2.

[0068] Fig.24 For the preparation of the product in Comparative Example 3 1 H NMR spectrum.

[0069] Fig.25 For the preparation of the product in Comparative Example 3 13 C NMR spectrum.

[0070] Fig.26 For the preparation of the product in Comparative Example 3 29 Si NMR spectrum.

[0071] Fig. 27The DSC curves of the products prepared in Application Example 1 and Comparative Application Example 1 are shown. DETAILED DESCRIPTION

[0072] The present invention will be further described in detail below in conjunction with specific implementation methods. Meanwhile, the embodiments described below are not intended to limit the present invention, and the various embodiments and features of the embodiments can arbitrarily form new embodiments.

[0073] Numerous specific details in the following description are used to better understand the present invention, but the present invention can still be implemented using other characteristic conditions different from those in the following description, including but not limited to steps or units that are not necessarily clearly listed.

[0074] The embodiment of the present invention provides an organic silicon material containing Si-H substituents and ethyl substituents, a preparation method and an application thereof, wherein 1 H NMR, 13 C NMR, 29 Its structure was characterized by Si NMR spectrum, gel permeation chromatography (GPC) and differential scanning calorimetry (DSC) to determine its composition, purity and low-temperature properties.

[0075] The embodiment of the present invention provides a method for preparing the above-mentioned organosilicon polymer material containing Si-H substituents and ethyl substituents, which specifically comprises the following steps:

[0076] The polymerization reaction device is inspected for air tightness and dried, and then a dichloromethane solution of a polymerization monomer, a capping agent and a chlorophosphazenic acid catalyst is added under the protection of dry inert gas, and the reaction is stirred at a constant temperature. After the reaction is completed, the system is cooled to room temperature, and a passivating agent is added to the system to neutralize the chlorophosphazenic acid catalyst. After sufficient stirring, the reaction product is transferred to a low molecular weight removal reaction vessel to remove the reactants and oligomers that have not been completely reacted in the crude reaction product, and then the solid residue in the product is removed by reduced pressure filtration to obtain a clear and transparent polysiloxane oligomer or copolymer fluid containing Si-H substituents and ethyl groups.

[0077] The chlorophosphonitrile acid catalyst used in the present invention can be prepared by using low-cost phosphorus pentachloride, ammonium chloride and the like as raw materials, and the reaction process is direct and simple. The prepared organic silicon fluid molecular chain segment containing Si-H substituents and ethyl substituents has uniform structure, good stability and is easy to store and transport.

[0078] In the present invention, the DV2TRVTJ0 type rotational viscometer of Brookfield Company of the United States is used to measure the viscosity of each liquid sample at 25°C and a shear rate of 30s -1 The dynamic viscosity under .

[0079] The Avance AV 400 NMR spectrometer from Bruker, Germany, was used to measure the1 H NMR spectra, about 10 mg of sample was dissolved in about 0.6 mL of deuterated chloroform (CDCl3) without internal standard, and the relaxation time D1 was 5 s. The Avance AVIII 500 solid-liquid dual-purpose NMR spectrometer of Bruker, Germany, was used to measure the 13 CNMR and 29 Si NMR spectroscopy, test 13 For C NMR, about 100 mg of sample was dissolved in about 0.6 mL of deuterated chloroform (CDCl3) without internal standard, and the relaxation time D1 was 3 s; 29 For Si NMR, about 150 mg of sample was dissolved in about 0.5 mL of deuterated chloroform (CDCl3) without internal standard, and the relaxation time D1 was 20 s;

[0080] A PL-GPC50 gel permeation chromatograph from Agilent Technologies, USA, was used with toluene as the mobile phase, polydimethylsiloxane with known molecular weight (molecular weight of 490, 6200, 15000, 34100, 64800, 95800, 219400, 384500 and 610000 g / mol) provided by American Polymer Standard Co., Ltd. was used as the standard, and a StyragleHT2 Toluene separation column was used to test the weight average molecular weight Mw, number average molecular weight Mn and polydispersity index PDI of the polymer. The toluene flow rate was 1.0 mL / min and the column temperature was 25°C.

[0081] DSC curves were recorded on a Netzsch DSC 214 (Netzsch, Germany) instrument at a flow rate of 40 mL / min under a nitrogen atmosphere. During the test, the temperature was increased from 40°C to 200°C at a heating rate of 10°C / min, then cooled from 200°C to -150°C at a rate of -10°C / min, and then heated from -150°C to 200°C at a heating rate of 10°C / min to obtain the DSC curves of the cooling stage and the heating stage.

[0082] The present invention is further described below in conjunction with specific embodiments. It should be noted that the various chemicals and reagents used in the examples are commercially available unless otherwise specified.

[0083] Example 1 Preparation of linear chlorophosphazene acid catalyst

[0084] The reaction device was preheated by blowing nitrogen. 5.35 g (0.1 mol) of ammonium chloride, 41.65 g (0.2 mol) of phosphorus pentachloride, 124.6 mL (1.0 mol) of 1,2,4-trichlorobenzene (the molar ratio of ammonium chloride to phosphorus pentachloride and 1,2,4-trichlorobenzene was 1:2:10), and 0.21 g of anhydrous magnesium chloride (the mass ratio of anhydrous magnesium chloride to phosphorus pentachloride was 1:200) were added to the reaction device in sequence; under nitrogen protection, the reaction mixture was heated to 165 ° C at a rate of 5 ° C / min and heated to reflux for 8 hours; after the reaction was completed, the reaction solution was poured into 249.2 mL of petroleum ether while hot (the volume of petroleum ether was twice the volume of 1,2,4-trichlorobenzene), and 32.2 g of blocky chlorophosphonitrile acid catalyst was obtained, and the calculated yield was 69%. The blocky chlorophosphazenic acid catalyst is dissolved in a dichloromethane solution to obtain a chlorophosphazenic acid-dichloromethane solution having an effective concentration of 2.5 wt % of chlorophosphazenic acid.

[0085] Example 2 Preparation of α,ω-dimethylsiloxy-terminated polydiethylsiloxane fluid

[0086] After the polymerization reaction device was inspected for air tightness and dried, 20.54 g (0.067 mol) of hexaethylcyclotrisiloxane, 3.00 g (0.022 mol) of 1,1,3,3-tetramethyldisiloxane and 0.4708 g of a 2.5 wt% chlorophosphazene solution of chlorophosphazene (the molar ratio of hexaethylcyclotrisiloxane to 1,1,3,3-tetramethyldisiloxane was 3.05:1, and the ratio of the effective mass of the chlorophosphazene catalyst to the sum of the masses of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane was 500×10 -6 :1). The reaction mixture was stirred at 50°C for 9 h for equilibrium polymerization. After the reaction was completed, the reaction mixture was cooled to room temperature and 0.0883 g (5.5 × 10 -4 mol) of hexamethyldisilazane as a passivating agent (the mass of hexamethyldisilazane is 7.5 times the effective mass of the chlorophosphazene acid catalyst), and stirring is continued for 9 hours, then the crude reaction product is transferred to a low-molecular-weight removal reaction vessel, and the temperature is gradually raised to 180° C. under a system vacuum degree of -101.2 kPa to remove unreacted reactants and oligomers in the crude reaction product, and the temperature is maintained for 5 hours and then cooled to room temperature, and the solid residue in the product is removed by filtration under reduced pressure to obtain 21.77 g of a clear and transparent α, ω-dimethylsiloxy-terminated polydiethylsiloxane fluid, which 1 H NMR, 13 C NMR, 29 SiNMR and GPC curves are shown in the attached Figure 1 ~Attached Figure 4The yield was calculated to be 93% based on the sum of the masses of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane.

[0087] By the attached Figure 1 It can be seen that if the area integral of Si-H is defined as 2, the area integral of the methyl group in the Et2SiO segment is 68.273, the area integral of the methylene group in the Et2SiO segment is 46.013, and the area integral of the terminal group (Me2HSiO 1 / 2 The area integral of the methyl group in -) is 12.132. The following two equations (eq. 1 and eq. 2) can be derived from the structural formula of the polymer.

[0088] 4m=46.013 (eq.1)

[0089] 6m=68.273 (eq.2)

[0090] By solving the above equation, we obtain the value of the degree of polymerization m = 11, that is, the structural formula of the prepared polymer is as shown in formula (I).

[0091]

[0092] Example 3 Preparation of α,ω-dimethylsilyloxy-terminated poly(dimethyl-diethyl)siloxane copolymer fluid

[0093] The polymerization reaction device was checked for air tightness and dried. Under the protection of dry nitrogen, 16.56 g (0.054 mol) of hexaethylcyclotrisiloxane, 10.68 g (0.036 mol) of octamethylcyclotetrasiloxane, 2.42 g (0.018 mol) of 1,1,3,3-tetramethyldisiloxane and 0.5932 g of 2.5 wt% chlorophosphazene acid-dichloromethane solution were added (the molar ratio of hexaethylcyclotrisiloxane to octamethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 3:2:1, and the ratio of the effective mass of the chlorophosphazene acid catalyst to the sum of the masses of hexaethylcyclotrisiloxane, octamethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 500×10 -6 :1). The reaction mixture was stirred at 50°C for 8 h. After the reaction was completed, it was cooled to room temperature and 0.0667 g (4.1×10 -4mol) hexamethyldisilazane as a passivating agent (the effective mass ratio of hexamethyldisilazane to chlorophosphazene acid catalyst is 4.5:1), and stirring is continued for 8 hours, and then the reaction product is transferred to a low-molecular-weight removal reaction vessel, and the temperature is gradually raised to 180° C. under a vacuum degree of -101.2 kPa to remove unreacted reactants and oligomers in the crude reaction product. After maintaining the temperature for 5 hours, the temperature is lowered to room temperature, and the solid residue in the product is removed by filtration under reduced pressure to obtain 24.70 g of a clear and transparent α, ω-dimethylsiloxy-terminated poly(dimethyl-diethyl)siloxane copolymer, which 1 H NMR, 13 C NMR and 29 Si NMR as attached Figure 5 ~Attached Figure 7 The yield was calculated to be 83% based on the sum of the weights of hexaethylcyclotrisiloxane, octamethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane added.

[0094] By the attached Figure 5 It can be seen that if the integral area of ​​Si-H is defined as 2, then the integral area of ​​Si-CH3 is 120. Since the molar ratio of methylene to methyl protons in the repeating Et2SiO chain is 2:3, according to the attached Figure 5 From the integrated areas of the two protons in the reaction mixture, it can be calculated that the degree of polymerization (m) of the Et2SiO segment and the degree of polymerization (n) of the Me2SiO segment are m=20 and n=18, respectively. That is, the structure of the prepared polymer is shown in formula (II).

[0095]

[0096] Example 4 Preparation of α,ω-dimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer fluid

[0097] The polymerization reaction device was checked for air tightness and dried. Under the protection of dry nitrogen, 16.56 g (0.054 mol) of hexaethylcyclotrisiloxane, 8.66 g (0.036 mol) of 1,3,5,7-tetramethylcyclotetrasiloxane, 2.42 g (0.018 mol) of 1,1,3,3-tetramethyldisiloxane and 0.5528 g of 2.5 wt% chlorophosphazene acid-dichloromethane solution were added (the molar ratio of hexaethylcyclotrisiloxane to tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 3:2:1, and the ratio of the effective mass of the chlorophosphazene acid catalyst to the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 500×10 -6:1). The reaction mixture was stirred at 50°C for 8 h. After the reaction was completed, it was cooled to room temperature and 0.1037 g (6.4×10 -4 mol) hexamethyldisilazane as a passivating agent (the effective mass ratio of hexamethyldisilazane to chlorophosphazene acid catalyst is 7.5:1), and stirring is continued for 8 hours, and then the reaction product is transferred to a low-molecular-weight removal reaction vessel, and the temperature is gradually raised to 180° C. under a vacuum degree of -101.2 kPa to remove the reactants and oligomers that have not been completely reacted in the crude reaction product. After maintaining the temperature for 5 hours, the temperature is lowered to room temperature, and the solid residue in the product is removed by filtration under reduced pressure to obtain 15.88 g of a clear and transparent α, ω-dimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer, which 1 H NMR, 13 C NMR and 29 Si NMR spectrum is attached Figure 8 ~Attached Fig.10 The yield was calculated to be 58% based on the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane.

[0098] 2.8 mg of 1,4-dioxane was used as an external standard and mixed with 9.7 mg of the prepared copolymer sample in CDCl3 solvent. 1 H NMR test (with Figure 8 ). If the integral area of ​​Si-H is 5, the integral area of ​​the H proton peak in 1,4-dioxane is 21.8. According to the structural formula of α,ω-dimethylsilyloxy-terminated poly(methyl hydrogen-diethyl)siloxane, the contents of hydrogen and methyl in the copolymer can be calculated using formula (eq.3) and formula (eq.4), respectively.

[0099]

[0100] In equation eq.3, S H refer to 1 The integrated area of ​​Si-H at δ = 4.7 ppm in the H NMR spectrum, m E is the mass of 1,4-dioxane, the number 88.11 is the molar mass of 1,4-dioxane, and the number 8 is the number of protons in 1 mol of 1,4-dioxane, m a is the mass of the sample added, S E for 1 The H NMR spectrum is located at δ = 3.7 ppm. The integrated area of ​​Si-H in 1,4-dioxane; in equation eq. 4, S Me yes 1 The integrated area of ​​Si-CH3 at δ = 0.16 ppm is located in the H NMR spectrum. Figure 8 Substituting the obtained area integral values ​​into equations eq.3 and eq.4, the contents of H and methyl were calculated to be 0.60% and 2.52%, respectively. According to the structural formula of the copolymer and equations (eq.3) and (eq.4), the contents of hydrogen and methyl in the copolymer can be expressed by equations (eq.5) and (eq.6), respectively.

[0101]

[0102] When solving equations (eq.5) and (eq.6), we obtain m≈5, n=3, and thus the structural formula of the obtained polymer is determined as shown in equation (III).

[0103]

[0104] Example 5 Preparation of α,ω-trimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer fluid The polymerization reaction device was checked for air tightness and dried. Under dry nitrogen protection, 16.56 g (0.054 mol) of hexaethylcyclotrisiloxane, 8.66 g (0.036 mol) of 1,3,5,7-tetramethylcyclotetrasiloxane, 2.92 g (0.018 mol) of hexamethyldisiloxane and 0.4502 g of 2.5 wt% chlorophosphazene acid-dichloromethane solution (the molar ratio of hexaethylcyclotrisiloxane to 1,3,5,7-tetramethylcyclotetrasiloxane and hexamethyldisiloxane was 3:2:1, and the ratio of the effective mass of the chlorophosphazene acid catalyst to the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and hexamethyldisiloxane was 400×10 -6 :1). The reaction mixture was stirred at 90°C for 8 h. After the reaction was completed, it was cooled to room temperature and 0.0844 g (5.2×10 -4 mol) hexamethyldisilazane as a passivating agent (the effective mass ratio of hexamethyldisilazane to chlorophosphazene acid catalyst is 7.5:1), and stirring is continued for 8 hours, and then the reaction product is transferred to a low-molecular-weight removal reaction vessel, and the temperature is gradually raised to 180° C. under a vacuum degree of -101.2 kPa to remove the reactants and oligomers that have not been completely reacted in the crude reaction product. After maintaining the temperature for 5 hours, the temperature is lowered to room temperature, and the solid residue in the product is removed by filtration under reduced pressure to obtain 22.59 g of a clear and transparent α, ω-trimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer, which 1 H NMR, 13 C NMR and 29 Si NMR spectrum is attached Fig.11 ~Attached Fig.13The yield was calculated to be 81% based on the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and hexamethyldisiloxane.

[0105] 2.9 mg of 1,4-dioxane was used as an external standard and mixed with 9.5 mg of copolymer sample in CDCl3 solvent. 1 H NMR spectrum test (attached Fig.11 ). If the integral area of ​​Si-H is defined as 7, the integral area of ​​the H proton peak in 1,4-dioxane is 47.2. According to the copolymer structure, the hydrogen content and methyl content in the copolymer molecule can be calculated by general formulas eq.3 and eq.4, and the results are 0.41% and 2.29% respectively.

[0106] According to the structural formula of the copolymer and formula (eq.3) and formula (eq.4), the contents of hydrogen and methyl in the copolymer can be expressed by formula (eq.7) and formula (eq.8), respectively.

[0107]

[0108] By solving equations (eq.7) and (eq.8), we obtain m=11, n=7, thereby determining that the structural formula of the prepared polymer is as described in formula (IV).

[0109]

[0110] Example 6 Preparation of α,ω-dimethylsiloxy-terminated polymethylethylsiloxane fluid

[0111] After the polymerization reaction device was inspected for air tightness and dried, 20.48 g (0.058 mol) of 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane, 1.56 g (0.012 mol) of 1,1,3,3-tetramethyldisiloxane and 0.6612 g of a 2.5 wt% chlorophosphazene solution of chlorophosphazene (the molar ratio of 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane to 1,1,3,3-tetramethyldisiloxane was 4.83:1, and the ratio of the effective mass of the chlorophosphazene catalyst to the sum of the masses of 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 750×10 -6 :1). The reaction mixture was stirred at 55°C for 6 h for equilibrium polymerization. After the reaction was completed, the reaction mixture was cooled to room temperature and 0.0827 g (5.1×10 -4mol) of hexamethyldisilazane as a passivating agent (the mass of hexamethyldisilazane is 5 times the effective mass of the chlorophosphonic acid catalyst), and continue stirring for 9 hours, then transfer the crude reaction product to a low molecular weight removal reaction vessel, gradually heat up to 180°C under a system vacuum of -101.2 kPa, remove the reactants and oligomers that have not been completely reacted in the crude reaction product, maintain at this temperature for 5 hours and then cool to room temperature, and remove the solid residue in the product by vacuum filtration to obtain 10.77g of clear and transparent α,ω-dimethylsiloxy-terminated polydiethylsiloxane fluid. Based on the sum of the masses of 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane, the yield is calculated to be 49%.

[0112] By the attached Fig.14 It can be seen that if the area integral of Si-H is defined as 2, the area integral of the methyl group in the ethyl group of the MeEtSiO segment is 92.000, the area integral of the methylene group in the MeEtSiO segment is 61.176, the area integral of the methyl group in the MeEtSiO segment is 91.908, and the area integral of the terminal group (Me2HSiO 1 / 2 -) is 12.010. Since the molar ratio of methylene to methyl protons in the repeating MeEtSiO chain is 2:3, according to the attached Fig.14 The integrated area of ​​the two protons in the MeEtSiO2 chain can be used to calculate the degree of polymerization (m) of the MeEtSiO2 chain segment to be 31. The structure of the prepared polymer is shown in Formula (V).

[0113]

[0114] Example 7 Preparation of α,ω-dimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer fluid

[0115] The polymerization reaction device was checked for air tightness and dried. Under the protection of dry nitrogen, 16.56 g (0.054 mol) of hexaethylcyclotrisiloxane, 8.66 g (0.036 mol) of 1,3,5,7-tetramethylcyclotetrasiloxane, 2.42 g (0.018 mol) of 1,1,3,3-tetramethyldisiloxane and 0.5528 g of 2.5 wt% chlorophosphazene acid-dichloromethane solution were added (the molar ratio of hexaethylcyclotrisiloxane to tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 3:2:1, and the ratio of the effective mass of the chlorophosphazene acid catalyst to the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane was 500×10 -6:1). The reaction mixture was stirred at 60°C for 8 h. After the reaction was completed, it was cooled to room temperature and 0.1037 g (6.4×10 -4 mol) hexamethyldisilazane as a passivating agent (the effective mass ratio of hexamethyldisilazane to chlorophosphazene acid catalyst is 7.5:1), and stirring is continued for 8 hours, then the reaction product is transferred to a low molecular weight removal reaction vessel, and the temperature is gradually raised to 180°C under a vacuum degree of -101.2 kPa to remove the reactants and oligomers that have not been completely reacted in the crude reaction product. After maintaining the temperature for 5 hours, the temperature is lowered to room temperature, and the solid residue in the product is removed by vacuum filtration to obtain 18.87 g of clear and transparent α,ω-dimethylsiloxy-terminated poly(methyl hydrogen-diethyl)siloxane copolymer. Based on the sum of the masses of hexaethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane, the yield is calculated to be 68%.

[0116] 4.2 mg of 1,4-dioxane was used as an external standard and mixed with 13.8 mg of the prepared copolymer sample in CDCl3 solvent. 1 H NMR test: According to the calculation method of Example 4, m≈6 and n=4 were calculated, and the structural formula of the prepared polymer was determined to be as shown in Formula (VI).

[0117]

[0118] Comparative Example 1: Using solid superacid ND-580 as a catalyst for the ring-opening polymerization of hexaethylcyclotrisiloxane

[0119] The polymerization reaction device was checked for air tightness and dried. Under the protection of dry nitrogen, 21.16 g (0.069 mol) of hexaethylcyclotrisiloxane and 3.09 g (0.023 mol) of 1,1,3,3-tetramethyldisiloxane were added. 0.2425 g of commercially available solid superacid ND-580 was used as a catalyst. The mass of the solid superacid was 0.01 times the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane. The reaction mixture was stirred at a constant temperature of 60°C for 9 hours. After the reaction is completed, the mixture is cooled to room temperature, the catalyst in the product is filtered out, and the filtrate is transferred to a low-molecular-weight removal reaction vessel, and the temperature is gradually raised to 180°C under a vacuum degree of -101.2 kPa to remove the unreacted reactants and oligomers in the crude reaction product. The temperature is maintained for 5 hours and then lowered to room temperature to obtain a clear and transparent α,ω-dimethylsiloxy-terminated polydiethylsiloxane fluid. 1 H NMR, 13 C NMR, 29 Si NMR and GPC curves are shown in the attached Fig.16 ~Attached Fig.19 The yield was calculated to be 90% based on the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane.

[0120] By the attached Fig.16 It can be seen that if the area integral of Si-H is defined as 2, the area integral of the methyl group in the Et2SiO segment is 74.898, the area integral of the methylene group in the Et2SiO segment is 50.092, and the area integral of the terminal group (Me2HSiO 1 / 2 -) is 11.845. Since the molar ratio of methylene to methyl protons in the repeating Et2SiO chain is 2:3, according to the attached Fig.16 The integrated area of ​​the two protons in the tantalum can be used to calculate the degree of polymerization of the Et2SiO chain segment, m=12, and the polymer structure is determined as shown in formula (VII).

[0121]

[0122] Comparative Example 2: Using concentrated sulfuric acid as a catalyst for the ring-opening polymerization of hexaethylcyclotrisiloxane

[0123] The polymerization reaction device was checked for air tightness and dried. Under the protection of dry nitrogen, 21.16g (0.069mol) of hexaethylcyclotrisiloxane and 3.09g (0.023mol) of 1,1,3,3-tetramethyldisiloxane were added. 0.2425g of 98wt% concentrated sulfuric acid was used as a reaction catalyst. The mass of concentrated sulfuric acid was 0.01 times the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane. The reaction mixture was stirred at a constant temperature of 60°C for 9h. After the reaction was completed, it was cooled to room temperature, the reaction solution was transferred to a separatory funnel, washed with saturated sodium bicarbonate solution to pH = 7, and the oil layer was recovered. Then, the oil layer product was transferred to a low molecular weight removal reaction vessel, and the temperature was gradually raised to 180°C under a vacuum degree of -101.2 kPa to remove the unreacted reactants and oligomers in the crude reaction product. After maintaining the temperature for 5 hours, the temperature was lowered to room temperature to obtain clear and transparent α,ω-dimethylsiloxy-terminated polydiethylsiloxane. 1 H NMR, 13 C NMR, 29 Si NMR and GPC curves are shown in the attached Fig. 20 ~Attached Fig.23 The yield was calculated to be 53% based on the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane.

[0124] By the attached Fig. 20It can be seen that if the area integral of Si-H is defined as 2, the area integral of the methyl group in the Et2SiO segment is 53.674, the area integral of the methylene group in the Et2SiO segment is 35.841, and the area integral of the terminal group (Me2HSiO 1 / 2 -) is 11.842. Since the molar ratio of methylene to methyl protons in the repeating Et2SiO chain is 2:3, according to the attached Fig. 20 The integrated area of ​​the two protons in the tantalum can be used to calculate the degree of polymerization of the Et2SiO segment, m=9, and the structural formula of the polymer is determined as shown in formula (VIII).

[0125]

[0126] Comparative Example 3: Using KOH as a catalyst for the ring-opening polymerization of hexaethylcyclotrisiloxane

[0127] The polymerization reaction device was checked for air tightness and dried. 14.72 g (0.048 mol) of hexaethylcyclotrisiloxane and 2.15 g (0.016 mol) of 1,1,3,3-tetramethyldisiloxane were added under the protection of dry nitrogen. 0.1687 g of KOH was used as a catalyst (the molar ratio of hexaethylcyclotrisiloxane to 1,1,3,3-tetramethyldisiloxane was 3:1, and the mass of KOH was 0.01 times the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane). The reaction mixture was stirred at a constant temperature of 60 ° C for 9 h. After the reaction was completed, it was cooled to room temperature, phosphoric acid was added dropwise to the system to neutralize to pH = 7, and the oil layer was recovered. Then the oil layer product was transferred to a low molecular weight removal reaction vessel, and the temperature was gradually raised to 180°C under a vacuum of -101.2 kPa to remove the unreacted reactants and oligomers in the crude reaction product. After maintaining the temperature for 5 hours, the temperature was lowered to room temperature to obtain a clear and transparent product. 1 HNMR, 13 C NMR and 29 Si NMR spectrum is attached Fig.24 ~Attached Fig.26 Based on the sum of the mass of hexaethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane, the yield was calculated to be 66%.

[0128] By the attached Fig.24 It can be seen that in 1 No proton peaks belonging to Si-H were observed in the H NMR spectrum, which means that there are no Si-H groups in the polymer. If it is assumed that all the terminal groups have become methyl groups, the terminal groups in the prepared polymer are Me3SiO 1 / 2-, the integrated area of ​​the methyl group from the terminal group is defined as 18, then the integrated area of ​​the methyl group in the Et2SiO segment is 104.313, and the integrated area of ​​the methylene group in the Et2SiO segment is 69.569. Since the molar ratio of methylene to methyl protons in the repeated Et2SiO segment is 2:3, according to the attached Fig.24 The integrated area of ​​the two protons in the reaction mixture can be used to calculate the degree of polymerization of the Et2SiO chain segment, m=28, and the structural formula of the prepared polymer is shown in formula (IX).

[0129]

[0130] Application Example 1 Preparation of diethylsilicon gel by hydrosilylation reaction

[0131] 2.00 g of commercially available double-end dimethylvinylsilyl-terminated polydiethylsiloxane of structural formula (X) was mixed with 0.6024 g of double-end dimethylsilyl-terminated poly(methylhydrogen-diethyl)siloxane copolymer of structural formula (VI) prepared in Example 7, wherein the molar ratio of Si-H to Si-CH=CH2 was 1.4:1; then a platinum vinyl complex (Castell catalyst) with a Pt content of 0.1 wt% and an effective Pt atomic concentration of 10 ppm was added as a catalyst, the reaction mixture was stirred evenly, and after vacuum removal of bubbles, it was cured at 80°C for 1 hour to obtain diethylsilicone gel prepared by hydrosilylation reaction. The prepared silica gel was subjected to DSC analysis, and the results are shown in the attached figure. Fig. 27 shown.

[0132]

[0133]

[0134] Preparation of dimethyl silicone gel by hydrosilylation using comparative example 1

[0135] 2.00 g of a commercially available double-end dimethylvinylsilyl-terminated polydimethylsiloxane of structural formula (XI) and 0.5167 g of a commercially available double-end trimethylsilyl-terminated poly(methyl hydrogen-dimethyl)siloxane copolymer of structural formula (XII) were mixed, wherein the molar ratio of Si-H to Si-CH=CH2 was 1.4:1; then a platinum vinyl complex (Castell catalyst) with an effective Pt atomic concentration of 10 ppm and a Pt content of 0.1 wt% was added as a catalyst, the reaction mixture was stirred evenly, and after vacuum removal of bubbles, it was cured at 80°C for 1 hour to obtain a dimethylsilicone gel prepared by a hydrosilylation reaction. The prepared silica gel was subjected to DSC analysis, and the results are shown in the attached figure. Fig. 27 shown.

[0136]

[0137] By the attached Fig. 27 It can be seen that the silicone gel generated by using the organosilicon material containing Si-H substituents and ethyl substituents prepared in Example 7 of the present application as a crosslinker for the hydrosilylation reaction and the organosilicon material containing Si-CH=CH2 substituents and ethyl substituents under the action of the Castel catalyst has a lower glass transition temperature than the silicone gel prepared by pure dimethylsiloxy chain segments (Comparative Example 1).

[0138] The performance tests were conducted on the polysiloxane fluids containing Si—H and ethyl substituents prepared in Examples 2 to 7 and Comparative Examples 1 to 3. The test results are shown in Table 1.

[0139] Table 1 Performance test results of polysiloxane fluids of Examples and Comparative Examples

[0140]

[0141] Note: 1. The design value of the degree of polymerization of diethylsiloxy chain segments or methylethylsiloxy chain segments in the polymer is calculated based on the amount of raw material hexaethylcyclotrisiloxane or 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane used; 2. The experimental determination value of the degree of polymerization of diethylsiloxy chain segments or methylethylsiloxy chain segments in the polymer is calculated based on 1 1H NMR calculation; 3. The design value of the polymerization degree of other siloxane segments in the polymer is calculated from the amount of the corresponding cyclotetrasiloxane used; 4. The experimental determination value of the polymerization degree of other siloxane segments in the polymer is calculated from 1 H NMR calculated.

[0142] As can be seen from Table 1, when KOH is used as a catalyst in Comparative Example 3, the viscosity of the product prepared reaches 18380 cP, indicating that KOH can effectively catalyze the ring-opening polymerization of hexaethylcyclotrisiloxane to obtain polydiethylsiloxane oligomers. 1 In the HNMR spectrum, no characteristic peak belonging to Si-H was found near δ=4.7ppm. This is because the active Si-H bond is incompatible with KOH and is very likely to undergo a dehydrogenation coupling reaction, resulting in the failure of the end-capping agent 1,1,3,3-tetramethyldisiloxane. Therefore, the polydiethylsiloxane fluid obtained in Comparative Example 3 has a large viscosity.

[0143] As can be seen from Table 1, although the yield of the prepared α,ω-dimethylsiloxy-terminated polydiethylsiloxane fluid is not much different from that of Example 2 when the ND-580 solid superacid in the comparative example is used as a catalyst at the same or similar polymerization monomer / capping agent ratio, the refractive index and viscosity of the two are quite different, indicating that the chlorophosphazene acid catalyst used in Example 2 has a higher reaction activity than the ND-580 solid superacid, and the polymer molecular weight prepared by using a smaller effective amount of the chlorophosphazene acid catalyst is larger.

[0144] Comparative analysis of the GPC curve of the product of Example 2 (attached Figure 4 ) and the GPC curve of the product obtained in Comparative Example 1 (attached Fig.19 ), it can be seen that the GPC curve of the product prepared in Example 2 presents a unimodal narrow distribution, and its PDI value is 1.46, while the GPC curve of the product prepared in Comparative Example 1 presents a complex multimodal distribution state and the PDI value reaches 1.62, indicating that although α, ω-dimethylsiloxy-terminated polydiethylsiloxane oligomers can be prepared by using ND-580 as a catalyst, the polymer composition is complex and the molecular weight distribution is uneven.

[0145] On the other hand, by Figure 1 Example 2 provided 1 H NMR spectrum shows that in the product prepared in Example 2, Si- H The group is similar to the methylene group in the silylethyl group (Si-C H 2CH3) group peak area ratio is 2 / 46.013, and when ND-580 in Comparative Example 1 is used as the catalyst, the Si- H The group is similar to the methylene group in the silylethyl group (Si-C H 2CH3) group peak area ratio is 2 / 50.092 (attached Fig.16 ), indicating that when chlorophosphazene acid is used as the catalyst, the Si-H content in the prepared product is higher.

[0146] It can also be seen from Table 1 that when sulfuric acid in Comparative Example 2 is used as a catalyst, the yield of the prepared product is only 53%, and the viscosity and refractive index of the product are also lower than those of the product prepared in Example 2. Although the PDI of the product in Comparative Example 2 is only 1.26, the GPC curve of Comparative Example 2 ( Figure 4 ) and the GPC curve of Comparative Example 2 ( Fig.23 ), it is not difficult to see that when sulfuric acid is used as a catalyst, the structure of the obtained product is complex. Although the polymer peak shape is narrow, in addition to the target polymer, the obtained polymer also contains multiple polymer components with lower molecular weight.

[0147] Comprehensive comparison of the data and corresponding spectra of Example 2 with Comparative Examples 1, 2 and 3 in Table 1 shows that α, ω-dimethylsiloxy-terminated polydiethylsiloxane fluid can be prepared using an acidic catalyst. Compared with solid acid, superacid and concentrated sulfuric acid, the use of linear chlorophosphazene acid as a catalyst for the ring-opening polymerization of hexaethylcyclotrisiloxane has a better state, a single structure and a narrow molecular weight distribution.

[0148] In summary, the present invention uses a chlorophosphazene acid catalyst to catalyze the ring-opening copolymerization of hexaethylcyclotrisiloxane or 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane alone or together with other ring bodies, and can successfully prepare a polymer containing Si-H substituents and ethyl substituents at both ends or in the side chain. The amount of phosphazene catalyst used is small, the reaction temperature is low, the reaction process is simple and controllable, the yield is high, and the molecular weight distribution of the prepared polymer is narrow.

[0149] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. An organosilicon material containing a Si-H substituent and an ethyl substituent, characterized in that: It has the structure shown below: Wherein, R1 is methyl, ethyl, phenyl, trifluoropropyl or H; R2 is methyl, ethyl, phenyl or trifluoropropyl; R3 is ethyl; R4 is methyl, phenyl or trifluoropropyl; R5 is methyl, phenyl, trifluoropropyl or H; m is the degree of polymerization of the R2R3SiO chain segment, and its value is 3 to 100; n is the degree of polymerization of the R4R5SiO chain segment, and its value is 0 to 50; at least one of R1 and R5 is H.

2. The method for preparing an organosilicon material according to claim 1, characterized in that: The following steps are involved: Under the protection of inert gas, a capping agent, a polymerizable monomer and a chlorophosphonitrile acid catalyst are added to a reactor, stirred, and a balanced polymerization reaction is carried out to obtain the organosilicon material; wherein the capping agent is disiloxane, and the polymerizable monomer is at least one of a cyclosiloxane containing an ethyl substituent, a polymerizable monomer containing a dimethylsiloxy chain segment, a polymerizable monomer containing a methylphenylsiloxy chain segment, a polymerizable monomer containing a methyltrifluoropropylsiloxy chain segment, a polymerizable monomer containing a diphenylsiloxy chain segment, or a methylhydrogencyclosiloxane polymerizable monomer, and in the combination of the capping agent and the polymerizable monomer, at least one compound contains a Si-H group and at least one compound contains an ethyl substituent.

3. The preparation method according to claim 2, characterized in that: The disiloxane includes at least one of 1,1,3,3-tetramethyldisiloxane, 1,1,1,3,3-pentamethyldisiloxane, hexamethyldisiloxane, octamethyltrisiloxane, decamethyltetrasiloxane, 1,1,3,3-tetramethyl-1,3-diphenyldisiloxane, or 1,1-dimethyl-1,1,3,3-tetraphenyldisiloxane; and / or, the cyclosiloxane containing an ethyl substituent includes at least one of hexaethylcyclotrisiloxane, octaethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-triethylcyclotrisiloxane or 1,3,5,7-tetramethyl-1,3,5,7-tetraethylcyclotetrasiloxane; And / or, the polymerizable monomer containing dimethylsiloxy chain segments includes at least one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, tetradecamethylcycloheptasiloxane, hexadecamethylcyclooctasiloxane, octadecadimethylcyclononasiloxane, eicosylcyclodecasiloxane or a mixed cyclosiloxane composed of dimethylsiloxy chain segments; And / or, the polymerizable monomer containing methylphenylsiloxane chain segments comprises at least one of cis- and trans-1,3,5-trimethyl-1,3,5-triphenylcyclotrisiloxane and mixtures thereof, four isomers of 1,3,5,7-tetramethyl-1,3,5,7-tetraphenylcyclotetrasiloxane and mixtures thereof, and four isomers of 1,3,5,7,9-pentamethyl-1,3,5,7,9-pentaphenylcyclopentasiloxane and mixtures thereof; And / or, the polymerizable monomer containing methyltrifluoropropylsiloxy chain segments comprises at least one of cis- and trans-1,3,5-trimethyl-1,3,5-tri(trifluoropropyl)cyclotrisiloxane and mixtures thereof, four isomers of 1,3,5,7-tetramethyl-1,3,5,7-tetra(trifluoropropyl)cyclotetrasiloxane and mixtures thereof, and four isomers of 1,3,5,7,9-pentamethyl-1,3,5,7,9-penta(trifluoropropyl)cyclopentasiloxane and mixtures thereof; And / or, the polymerizable monomer containing diphenylsiloxy chain segments comprises at least one of hexaphenylcyclotrisiloxane, octaphenylcyclotetrasiloxane and decaphenylcyclopentasiloxane; And / or, the methylhydrogencyclosiloxane includes at least one of 1,3,5-trimethylcyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5-trimethylcyclotetrasiloxane, 1,3-dimethylcyclotetrasiloxane, 1,5-dimethylcyclotetrasiloxane, 1,3,5,7,9-pentamethylcyclopentasiloxane or 1,3,5,7,9,11-hexamethylcyclohexasiloxane.

4. The preparation method according to claim 2 or 3, characterized in that: The molar ratio of the end-capping agent to the polymerizable monomer is 0.05 to 1:

1.

5. The preparation method according to claim 4, characterized in that: The ratio of the effective mass of the chlorophosphonitrile acid catalyst to the sum of the mass of the end-capping agent and the polymerized monomer is (10-2000)×10 -6 :

1.

6. The preparation method according to claim 2, characterized in that: The equilibrium polymerization reaction temperature is 40-120° C., and the reaction time is 4-12 hours.

7. The preparation method according to claim 2, characterized in that: After the equilibrium polymerization reaction is completed, a passivator is added to the reaction system to neutralize the chlorophosphazene acid catalyst to obtain a crude reaction product; then, the unreacted reactants and oligomers in the crude reaction product are removed, and the solid residue is removed by vacuum filtration to obtain the organosilicon material.

8. The preparation method according to claim 7, characterized in that: The passivator is at least one of hexamethyldisilazane, magnesium oxide, aluminum oxide, zinc oxide or ferric oxide, and the ratio of the mass of the passivator to the effective mass of the chlorophosphonitrile acid catalyst is 3 to 10:

1.

9. The preparation method according to claim 7, characterized in that: The conditions for removing the unreacted reactants and oligomers in the crude reaction product are: a removal temperature of 150 to 250° C., a system vacuum degree of -101.3 to -90 kPa, and a removal time of 4 to 12 hours.

10. Use of the organosilicon material according to claim 1 as a crosslinking agent in the preparation of organosilicon polymer materials or composite materials.